Influencing Mechanism of Electrochemical Treatment on Preparation of CNTs-grafted on Carbon Fibers - SONG Lei; CHEN Ji-qiang; FAN Wen-xin; WANG Cheng-guo (Cailiao gongcheng, 2017)
Based on electrochemical anodic oxidation, an innovative technique was developed to efficiently obtain the uniform catalyst coating on continuous carbon fibers. Through systematic investigation on the effect of electrochemical modified strength on the physical and chemical characteristics of carbon fiber surface, catalyst particles and the morphology of CNTs-grafted carbon fibers, tensile strength of multi-scale reinforcement and the interlaminar shear strength of its reinforced composites, the electrochemical modification process on carbon fibre surface was optimized. The results show that the morphology and distribution of catalyst particles not only affect the morphology of CNTs deposited on the surface of carbon fibres,but also affect the mechanical properties of multi-scale reinforcement and its reinforced composites of CNTs-grafted carbon fibers.